Ultrastructural changes in renal parenchyma with renal cell carcinoma - Pasichnyk, S.; Stakhovsky, O.; Gozhenko, A.; Pasichnyk, M.; Voronina, O. (Journal of Education, Health and Sport, 2018)
In recent years, there has been a significant increase in incidence of the renal cell carcinoma (RCC). In the structure of cancer, this pathology is on 10th place. The surgical treatment is the most radical and most effective method of management of this disease. Currently renal resection has become a desirable alternative to radical nephrectomy for tumors of the T1 stage [6, 7, 8, 9]. Nephron-sparing interventions, compared to radical nephrectomy, showed an equivalent cancer outcome in tumors < 4 cm in diameter [1, 10]. However, there is an opinion [2] that in the intact part of the organ due to an increased functional load various pathomorphological changes may occur [3, 4 ,7]. Although, it is believed that in this cohort of patients there are no pathomorphological changes and only in rare cases, distant functional changes can be observed [5, 2].